THERMO GRAVIMETRIC AND INFRARED SPECTRAL STUDIES FOR RAPID EVALUATION OF ROCK PHOSPHATES (Biological Sciences - PJSIR, 2022)
Thermal, infrared spectral and chemical analyses have been carried out on fourteen rock phosphate samples fromfive deposits in Hazara, North West Frontier Province (NWFP), Pakistan. Samples with high phosphate content haveshown less than 3% loss in weight on ignition and a set of two characteristic medium intensity absorption bands in therange 1460-1420cm'. On the other hand ores samples with low phosphate content have shown high loss in weight onignition and only one absorption band around 1460-1420cm' in their infrared spectra. The analytical data describedand discussed in this paper suggests that TGA/DTA and infrared spectral techniques may be used as a rapid means forthe preliminary selection of ore-grades, in place of conventional techniques.